2011
DOI: 10.1007/s10815-011-9556-2
|View full text |Cite
|
Sign up to set email alerts
|

Reliable preimplantation genetic diagnosis in thawed human embryos vitrified at cleavage stages without biopsy

Abstract: Reliable genetic diagnosis can be performed in thawed human embryos vitrified without biopsy. However, further research is required to support this conclusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…For women with fewer than three good-quality embryos, embryo transfer was at Day 2-3. Supernumerary good-quality embryos were cryopreserved (Zhang et al, 2011). The number of embryos transferred was determined according to the provincial guidelines at that time: up to two or three embryos and never more than three.…”
Section: Embryo Culturementioning
confidence: 99%
“…For women with fewer than three good-quality embryos, embryo transfer was at Day 2-3. Supernumerary good-quality embryos were cryopreserved (Zhang et al, 2011). The number of embryos transferred was determined according to the provincial guidelines at that time: up to two or three embryos and never more than three.…”
Section: Embryo Culturementioning
confidence: 99%
“…Blastocyst hatching is an important step in the sequence of physiologic events that end up in implantation [ 36 ]. Previous studies demonstrated that the small hole that must be created in the zona for embryo biopsy after thawing may also help the embryo to hatch [ 37 ]. Although hatching effect on clinical outcomes remains unknown, some studies hypothesized that a fully hatching embryo was more friable and less likely to implant that a non-fully hatching embryo [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Embryonic development is assessed and the embryos are vitrified 2 days after ICSI. A previous study showed that freezing embryos on day 2 or 3 post-fertilization doesn't have any significant effect on embryo survival and PGD test success rates [10,24].…”
Section: Methodsmentioning
confidence: 99%